Ionogels based on a single ionic liquid for electronic nose application - Gonçalves, Wellington B. (2022)
165186/2015-1 307501/2019-1 424027/2018-6 grant reference SCENT-ERC-2014-STG-639123 (2015-2020) UIDB/04378/2020 POCI-01-0145-FEDER-007728